FAKTOR RISIKO KEJADIAN MALARIA PADA MASYARAKAT DI WILAYAH KERJA PUSKESMAS KRUENG SABEE KABUPATEN ACEH JAYA - Haris Ferdinal Setiawan; Irma Hamisah; Farrah Fahdhienie (Poltekkes Kemenkes Jambi, 2021)
Background: Malaria is still a public health problem that has an impact on the decline in productivity and quality of life in the community. Aceh Jaya district is a malaria-endemic area. Identification of risk factors causing malaria transmission needs to be done to break the chain of transmission so that prevention and control measures can be carried out appropriately. This study aimed to determine the risk factors for malaria in the community in the working area of the Krueng Sabee Health Center, Aceh Jaya Regency Method: This research was a descriptive-analytic with a case-control study design. The case group was malaria-positive sufferers based on the results of laboratory examinations from January 2018 to March 2019. The control group was people who did not suffer from malaria. The research sample consisted of 21 cases and 21 controls. Collection in January 2020 with observations and interviews. The analysis was used in univariate and bivariate. Using logistic regression statistical test. Result: The results of the univariate analysis showed that there were cases of malaria in men (58.6%), risky occupations (78.9%), the habit of going out at night (70.6%), not using mosquito nets (64.5%), not using wire netting (59.3%), not using insecticides (76.9%) and lack of knowledge (65.3%). The results of statistical tests can be concluded that there is a relationship between work (OR=4; p value=0.034), habit of going out at night (OR=4.2; p value=0.032), use of mosquito nets (OR=5.6; p value=0.014), use of insecticides (OR =5.4; p-value = 0.026) and knowledge (OR = 4; p-value = 0.034) with the incidence of malaria. Conclusion: There was a relationship between work variables, night out habits, the use of mosquito nets, the use of insecticides, and knowledge of the incidence of malaria